Salvaguardas, “dumping” e subsídios: a perspectiva brasileira - C, José Tavares de Araújo (1989)
This paper argues that the establishment of a safeguards code is one of the basicissues to be faced by the present GATT round of negotiations. Section II discusses the roleof safeguards measures as instruments of protection, shows the problems that arise from thelack of a code on such matter, and indicates the feasible options for regulation. Section IIIanalyses the operation of the antidumping and subsidies codes during the eighties, with emphasison the impacts of the actions taken by other countries against Brazilian exports, andreveals the interplay of these codes with other instruments of protection used by developedcountries. Section IV summarizes the main points of the article. JEL Classification: F13.